البعد السياسي والأمني للشراكة الأورو- متوسطية - رشيد محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول البحث الشراكة الاورو- متوسطية من حيث تاريخ هذه العلاقة بين الطرفين العربي والأوربي ومراحل تطور هذه العلاقة والاتفاقيات الموقعة بين الطرفين, ودوافع كلٍّ منهما إلى عقد شراكة فيما بينهما, وماهي الآثار السياسية والأمنية لهذه الشراكة, وما هي العوامل التي تؤثر على هذه الشراكة, وكذلك يتطرق البحث للدور الأمريكي المؤثر على العلاقة العربية والأوربية, وكذلك مستقبل هذه الشراكة في ظل المتغيرات الإقليمية والدولية وفي ظل البوادر الظاهرة للنظام العالمي الجديد. This research focuses the Euro-Mediterranean partnership in terms of the history of this relation between the Arab and the European sides, and the development of this relation and the agreement between these parties. It also studies the motivations of both to build a partnership between them, the political and security consequences of such partnership, and the factors that affect it. This research also addresses the US role in this Arab-European relation, and the future of this partnership in the light of regional and international changes and under signs of the new world order.